Interaksi Siswa dengan Guru dalam Menciptakan Situasi yang Kondusif di SD Al-Ittihadiyah Laut Dendang - Afrahul Fadhila Daulai; Tania Salsabila; Dhini Maharani; Mila Sapitri Rambe; Lili Kurniasih; Hasraful Fadila Tinendung (FKIP, Universitas Palangka Raya, 2025)
The problem of this research is how teachers and students interact in creating a conducive situation for learning in class II of Al-Ittihadiyah Elementary School. The aim of this research is to analyze how students interact with teachers to create a comfortable situation in the classroom when learning takes place. The research method used is a qualitative descriptive research method with the research objects being teachers and students in sociology learning. The research results show that the social interaction between teachers and students is good. In good conditions, the interaction between teachers and students looks friendly, the learning situation is enthusiastic, and there is teacher apperception for students. From the conclusions of the research findings, the interactions carried out by teachers and students in class II show that the teacher's performance in creating a conducive classroom climate is said to be good, which can be seen from the teacher being able to develop himself to be more professional and improving the quality of students' learning. The creativity of teachers in creating effective learning situations in class II at SD Al-Ittihadiyah. The methods used by teachers include lectures, questions and answers, and discussions. The media used include whiteboards and canvas. Factors inhibiting teacher creativity include the complete facilities and infrastructure of the school.